A First‐Principles Study on ABBr3 (A = Cs, Rb, K, Na; B = Ge, Sn) Halide Perovskites for Photovoltaic Applications. Issue 12 (8th September 2022) - Saikia, Dibyajyoti; Alam, Mahfooz; Bera, Jayanta; Betal, Atanu; Gandi, Appala Naidu; Sahu, Satyajit
Abstract: Perovskite solar cells (PSCs) have received intensive attention and demonstrated power conversion efficiency (PCE) as high as 25.8%. Concerning Pb toxicity and the instability of organic elements, all inorganic lead‐free perovskites (ILPs) have been extensively studied to achieve comparable or greater photovoltaic performance. To develop ILPs as an alternative for solar cell (SC) applications, first‐principles calculations of ABBr3 perovskites (A = Cs, Rb, K, and Na, and B = Sn, and Ge) is performed. Structural, electronic, and optical properties are systematically studied to probe the potential for photovoltaic applications. These ILPs exhibit a direct bandgap in the range of 1.10–1.97 eV, which is highly beneficial for absorbing solar energy. Furthermore, these ILPs demonstrated significant optical absorption (over 10 5 cm −1 ) in the UV–Vis spectrum. These results will help design high‐performance lead‐free PSCs. Abstract : The structural, electronic, and optical properties of lead‐free all inorganic ABBr3 (A = Cs, Rb, Sn; B = Sn, Ge) perovskites have been studied using first principles calculations. The studied perovskites exhibit direct band gaps in the range of 1.10–1.97 eV along with significant optical absorption in the UV–Vis region. Among the studied compounds Cs‐based perovskites exhibit superior thermodynamic stability and optoelectronic properties.